Penyuluhan dan Demonstrasi Pembuatan Eco-Enzyme sebagai Solusi Pengelolaan Sampah Organik Rumah Tangga pada Ibu Rumah Tangga di Desa Menanti Kecamatan Lubai: Counseling and Demonstration of Eco-Enzyme Production as a Solution for Household Organic Waste Management among Housewives in Menanti Village, Lubai District - Dyah Ayu Nuraini; Putri Wahyu Ningsih; Rismawati; Nurul Shafwa Luthfia; Devita Mutiara; Raykhan Yoga Pratama; Ayu Prameswari (Poltekkes Kemenkes Yogyakarta, 2025)
The increasing volume of improperly managed household organic waste can lead to environmental pollution and elevate the risk of public health problems, including the proliferation of disease vectors and the deterioration of environmental sanitation quality. This condition was still identified in Menanti Village, Lubai District, where the community, particularly housewives, had limited knowledge and skills regarding household organic waste management. This community service activity aimed to improve the knowledge and skills of housewives in processing organic waste into eco-enzyme as an environmentally friendly and beneficial product. The program was conducted on June 3, 2025, in Menanti Village using an educative-participatory approach through counselling, demonstrations, and hands-on practice in eco-enzyme production. The target participants were housewives recruited through coordination with the village government and local community groups. The activity stages included preparation of materials and educational media, counselling regarding the benefits of eco-enzyme, demonstration of the production process, direct participant practice, and evaluation through skill observation and participant responses. The results showed that participants were able to understand the concept of eco-enzyme, follow the fermentation stages correctly, and independently practice eco-enzyme production using household organic waste. In addition, the activity increased community awareness regarding the importance of environmentally based household waste management and the utilization of organic waste as a value-added product. This activity was effective as a community empowerment effort to support clean and healthy living behaviours and sustainable environmental management at the household level.